2007
DOI: 10.1016/j.jneumeth.2006.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spectral analysis methods for characterizing brain oscillations

Abstract: Spectral analysis methods are now routinely used in electrophysiological studies of human and animal cognition. Although a wide variety of spectral methods has been used, the ways in which these methods differ are not generally understood. Here we use simulation methods to characterize the similarities and differences between three spectral analysis methods: wavelets, multitapers and P episode . P episode is a novel method that quantifies the fraction of time that oscillations exceed amplitude and duration thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 46 publications
(46 reference statements)
0
105
0
1
Order By: Relevance
“…Visual inspection of LFP signals revealed that unlike the long, continuous trains of oscillations seen in the rodent hippocampus during "active states," oscillatory activity occurred in intermittent bouts separated by desynchronized, nontheta activity, similar to the activity previously described in the human hippocampus (8). Previous studies have evaluated the incidence of oscillatory components in continuous LFP data using the P episode measure (8,(25)(26)(27), which detects episodes of oscillatory activity exceeding amplitude and duration thresholds at each frequency of interest while ignoring the transient voltage fluctuations that may accompany artifacts or evoked potentials. We used this method to detect bouts of oscillatory activity in the theta frequency range that exceeded three cycles in duration and determined the incidence of these bouts across blocks of the VPLT.…”
Section: Resultsmentioning
confidence: 89%
“…Visual inspection of LFP signals revealed that unlike the long, continuous trains of oscillations seen in the rodent hippocampus during "active states," oscillatory activity occurred in intermittent bouts separated by desynchronized, nontheta activity, similar to the activity previously described in the human hippocampus (8). Previous studies have evaluated the incidence of oscillatory components in continuous LFP data using the P episode measure (8,(25)(26)(27), which detects episodes of oscillatory activity exceeding amplitude and duration thresholds at each frequency of interest while ignoring the transient voltage fluctuations that may accompany artifacts or evoked potentials. We used this method to detect bouts of oscillatory activity in the theta frequency range that exceeded three cycles in duration and determined the incidence of these bouts across blocks of the VPLT.…”
Section: Resultsmentioning
confidence: 89%
“…Correspondingly, the choice of spectral method for the analysis of electrophysiological data has also been highly debated [Bruns, 2004; Le Van Quyen and Bragin, 2007; Le Van Quyen et al, 2001; van Vugt et al, 2007]. In the first part of this work, we developed a method based on bootstrapping across trials, which served two purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The power threshold (p T ) was set to the 95th percentile of the theoretical probability distribution. The proportion of time in which significant oscillations were detected within a 5 min sleep was termed P episode (Caplan and Glaholt, 2007;Caplan et al, 2001Caplan et al, , 2003van Vugt et al, 2007).…”
Section: Discussionmentioning
confidence: 99%